Management of patients with aphthous-like ulcers related to aplastic anaemia in the COVID-19 pandemic era through teledentistry: A case report - Lani Berlina Talahatu; Bima Ewando Kaban; Nurina Febriyanti Ayuningtyas; Intan Noha Brilyanti; Adiastuti Endah Parmadiati; Desiana Radithia; Aulya Setyo Pratiwi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Aplastic anaemia is a disease that occurs when the body fails to produce enough blood cells. Oral lesions, such as canker sores, are often used as an early marker of this disease condition. In the COVID-19 pandemic era, a teledentistry method is expected to assist in the management of patients with various diseases including aplastic anaemia. Purpose: This case report discusses the management of patients with aphthous-like ulcers related to aplastic anaemia in a 34-year-old woman, based on history, clinical examination, and blood tests through teledentistry. Case: The patient complained of a bleeding wound on the inner left cheek and corner of the left lip that appeared one month ago. There was an ulcer lesion that was bleeding easily in the buccal mucosa sinistra and the angular sinistra, as well as macules lesion on her hand and foot. The complete blood count test exhibits a low platelet level. Case management: The diagnosis was an aphthous-like ulcer related to aplastic anaemia. Patient was treated with topical antiseptic and anti-inflammatory mouthwashes for the oral lesions, as well as collaboration with the medical team. The lesions improved after the patient received a blood transfusion and drug therapy from the internist while she was hospitalized, but the lesions reappeared in other locations in the oral cavity when the platelet level dropped. Conclusion: Management of oral manifestations in patients with aphthous-like ulcers related to aplastic anaemia in the COVID-19 pandemic era can be done through teledentistry. However, this requires sensitivity from the dentist, patient compliance in following instructions, and the involvement of a multidisciplinary approach, such as collaboration with internists to achieve recovery. Delay in detecting and treating aplastic anaemia will lead to death, as in this case.